2016
DOI: 10.1177/1933719115623643
|View full text |Cite
|
Sign up to set email alerts
|

Depo-Provera Versus Norethisterone Acetate in Management of Endometrial Hyperplasia Without Atypia

Abstract: The objective of this study was to assess effectiveness and safety of Depo-Provera (medroxyprogesterone acetate) in treatment of endometrial hyperplasia (EH) and to compare it with norethisterone acetate (NETA) as an oral progestogen treatment. One hundred forty six women aged 35 to 50 years with abnormal uterine bleeding and diagnosed as having EH were randomized to receive either Depo-Provera, one injection every 3 months for 6 months (2 doses), or oral cyclic NETA, 15 mg daily for 14 days per cycle for 6 mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 27 publications
0
2
0
3
Order By: Relevance
“…43 Endometrial hyperplasia regressed in 91.8% of women after 6 months of treatment with depot medroxyprogesterone acetate. 44 Depot medroxyprogesterone acetate, however, can cause weight gain and lower bone mineral density. 45 The 52-mg LNG-IUD, which delivers 20 mcg of LNG per day, has been studied for both the pre-vention and treatment of endometrial pathology in women being treated with tamoxifen.…”
Section: Discussionmentioning
confidence: 99%
“…43 Endometrial hyperplasia regressed in 91.8% of women after 6 months of treatment with depot medroxyprogesterone acetate. 44 Depot medroxyprogesterone acetate, however, can cause weight gain and lower bone mineral density. 45 The 52-mg LNG-IUD, which delivers 20 mcg of LNG per day, has been studied for both the pre-vention and treatment of endometrial pathology in women being treated with tamoxifen.…”
Section: Discussionmentioning
confidence: 99%
“…Many of the data on the use of progestational agents are derived from the treatment of patients with simple and complex hyperplasia, often in the absence of cellular atypia. In those populations, treatment with progestational agents has been shown to result in high rates of regression (29)(30)(31)(32)(33)(34)(35)(36)(37). Although there are more limited data on the treatment of EIN-AEH with progestational agents, studies have found high rates of disease regression in patients who are not candidates for definitive surgical management and, instead, are managed with more conservative approaches.…”
Section: Nonsurgical Managementmentioning
confidence: 99%
“…Під час вивчення стану рецептивності встановлено найменший рівень рецепторів естрадіолу і прогестерону при атиповій гіперплазії ендометрія. Зниження рівня рецепторів у гіперплазованому ендометрії можна розглядати як несприятливий прогностичний фактор, що відображає низьку ефективність потенційної гормональної терапії [30,35,37].…”
Section: д и с т а н ц і й н е н а в ч а н н яunclassified
“…новлено, що одним з важливих геномних порушень при раку ендометрія є мікросателітна нестабільність -наслiдок iнактивації генів системи репарацiї неспарених нуклеотидів, зокрема MSH2, MSH3, MSH6, MLH1, PMS2, EXO1. Це свідчить про високу вірогідність виникнення трансформівних мутацiй в усьому геномі [31,35].…”
Section: д и с т а н ц і й н е н а в ч а н н яunclassified